Efek Pemaparan Deltamethrin pada Broiler Terhadap Aktivitas Enzim Alanin Aminotransferase, Aspartat Aminotransferase dan Gambaran Histopatologi Hepar - Nemay Anggadewi Ndaong; Agustina Dwi Wijayanti; Sitarina Widyarini (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
The purpose of this study is to determine the effects of deltamethrin exposure on the Broiler’s liver histopathological feature, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) enzyme activity. Fourty DOC Broilers strain New Loghman are divided into four group of ten and they were adapted for 5 days prior to the treatment. Group I (KI) is a control group, group II were given 20 mg/L deltamethrin, group III were given 10 mg/L deltamethrin and exposure deltamethrin concentration 10 mg/L and group IV were given 5 mg/L delthametrin. Deltamethrin was mixed with drinking water and then was given to the treatment group for 30 days. Blood samples were taken on day 0, day 15 and day 30 of treatment to determine of ALT and AST enzyme activity. On day 35, all animal were sacrificed, liver were taken out and fixed in 10% of buffer formalin for microscopic examination. Results of the AST enzyme activity shows that exposure to 20 mg/L and 10 mg/L deltamethrin for 30 days resulted in the histopathological changes of the liver, such as, fatty degeneration, necrosis on liver cells, inflamation of the liver, and necrosis on liver cells without the infiltration of inflamation cells. It is conclude that exposure to 20 mg/L deltamethrin for 30 days resulted in an increase in AST enzyme activity which is supported liver histopathological changes: fatty degeneration, necrosis, inflamation, and necrosis on liver cells without the infiltration of inflamation cells.